Transfer of patients in hospital units: impacts on nursing workload - Trovó, Simone Aparecida; Cucolo, Danielle Fabiana; Perroca, Márcia Galan (Revista da Escola de Enfermagem da USP, 2021)
Objective: To measure the average time spent by the nursing team in transferring patients; to compare the activities observed during the performance of this intervention with those described by the Nursing Interventions Classification and to investigate the intensity of its influence on the workload. Method: Observational study using timekeeping software conducted in two hospitals in the northwest region of the State of São Paulo. 200 patient transfers were monitored by the team using two validated instruments. Results: The average time spent by nurses on transfers ranged from 9.3 (standard deviation = 3.5) to 12.2 (standard deviation = 2.5) minutes and by assistants/ technicians between 7.1 (standard deviation = 2,8) and 11.0 (standard deviation = 2.2) minutes. 63 transfers made by nurses and 87 by assistants/technicians were considered qualified (>70% of the score). The team expended 19.3 to 29% of the working day time in this intervention. Conclusion: The transfer of patients has an impact on the workload of the team and needs to be considered in the measurement of nursing activities for the calculation and distribution of personnel to improve the quality and continuity of care.